All Dry Bottom‐Up Assembly of Omniphobic Interfaces. Issue 12 (30th April 2020) - Ghaleni, Mahdi Mohammadi; Kaviani, Shayan; Rajwade, Kimya; Bavarian, Mona; Perreault, François; Nejati, Siamak
Abstract: Creating reentrant structures on flexible and porous substrates is a significant challenge for the scalable fabrication of omniphobic membranes. The design of such membranes requires control over the surface topography and chemistry of the interfacial domains. Here, a continuous bottom‐up method, based on initiated chemical vapor deposition, is developed to enable the fabrication of flexible omniphobic membranes. The developed membranes hinder the intrusion of droplets of low surface energy liquids (e.g., ethanol) colliding with the surface at a velocity of about 2 m s −1 . The stable wetting resistance of the membranes allows for the desalination of low surface energy synthetic and municipal wastewater streams. Abstract : An all‐dry bottom‐up method is developed for the assembly of polymer reentrant structures on porous and flexible substrates. The designed interfaces show exceptional wetting resistance against low polarity liquids. Through this approach, vapor‐gap separation media can be synthesized for desalination and purification of challenging wastewater streams. This scheme can be adapted for large‐scale manufacturing of omniphobic and antiwetting membranes.